LES FACTEURS PREDICTIFS DE RECIDIVE DU KYSTE HYDATIQUE DU FOIE - BENDJEDOU Tassbih; BENDIB Maroua (My University, 2023)
Hydatidosis is a parasitic infection caused by Echinococcus granulosus, It is an endemic desease that covers all countries around the meditertanean, it can affect all organs without exception, especially the liver. Its importance and severity depends not only on the high endemicity it presents but also on its complication rate and recurrence, which is maintained thanks to several factors. This work was conducted to determine these possible predictive factors of the recurrence of the hydatid cyst of the liver and to propose effective solutions in ordre to reduce the impact of this problem. This is a retrospective study spread out for five years, where we studied 64 opearted patients with HC of the liver. The results of this study show that the recurrence rate of hydatid cyst of the liver is 23% affecting young adults with an average age of 29 years predominant in femals. The majorities of patients are from urban areas. The complicated form represents 20% of recidivant cases. The clinical expression lack of specificity. These are dominated by the right upper quadrant pain and vomiting. The most common complication was represented by jaundice. Ultrasound is the main paraclinical examination that allows the diagnosis. Cysts are of type III in 42.3 % of cases, localized in between the right and left lobes in 46.7 % of cases. Multivariate analysis showed that voluminous cysts (larger than 80mm) were a predictive factor of recurrence. Surgical treatment is performed in all cases. Medical therapy was only used in 2 recurrent cases in association with surgery. Laparotomy was performed in all patients. Conservative procedure, which is the resection of the bulging dome, was used in 80% of the recurrent cases, however a radical treatement was performed in only 20% of the cases even though it may offer the lowest recurrence rate. 128 Our results are satisfactory with weak rate of morbidity (9.4%), and no mortality. The ignorance of people concerning this disease remains a worrying probleme hence the need for awareness spreading and education because after all prophylactic mesures remains the best treatement in these endemic areas.
132 p.